Development of in vitro assays for detection of anthelmintic resistance in cattle nematodes : a thesis presented in partial fulfilment of the requirements for the degree of Master of Science (Animal Science) at Massey University, Palmerston North, New Zealand - Mshanga, Deogratius Andrew (Massey University, 2007)
The principle aim of the current research was to modify the larval development assay (LDA) for use with Cooperia from cattle. A series of experiments were conducted in order to modify the LDA protocol to determine the most appropriate culture media and incubation temperature. These initial experiments concluded that, of the protocols examined, a culture medium of 1/8th the concentration of E. coli (EC) + 1/4th the concentration of yeast extract (YE) as generally used to culture sheep nematodes, at a culture temperature of 18ºC, resulted in the optimum number of Cooperia larvae developed to the third larval stage (L3). However, the number of eggs that developed to L3 was still generally low. A comparison was then made using isolates from a farm with a history of resistance in Cooperia to ivermectin (IV) and benzimidazoles (BZ) and two farms with a history of no resistance in this parasite. These experiments were undertaken using 1/8EC + 1/4YE media protocol and 1/2EC + 1/2YE concentration of the standard culture media for sheep nematodes. These three isolates were cultured at temperature of 18ºC and 25 ºC in the commercially available DrenchRite® 96-well microtitre assay plates which contained BZ, levamisole (LV) and IV in doubling dilutions within an agar matrix. The LD50 values were determined from a dose response curve. The resulting LD50 values were very variable, especially for the IV analogues. There was no obvious difference between the resistant and susceptible farms for the LD50 values of BZ or IV. A secondary aim of this research was to investigate the potential usefulness of the larval feeding inhibition assay (LFIA). This was adopted as published and it was determined it could be used to distinguish between susceptible and resistant Teladorsagia circumcincta with a resistance ratio of at least six. This research concluded that further research is required to fully optimise the LDA for Cooperia in cattle but adequate dose response curves were determined to indicate it struggles to distinguish BZ and IV resistance. The LFIA deserves to be further investigated as it offers some scope to detect ivermectin resistance in cattle nematodes as the dose response curves demonstrated a good repeatability for T. circumcincta from sheep. Comparing LDA and LFIA, both assays seemed to be useful but the latter was considered to have greater potential.
Keywords: Cattle nematodes; Larval development assay; Cooperia larvae; Fields of Research::300000 Agricultural, Veterinary and Environmental Sciences::300500 Veterinary Medicine::300503 Epidemiology